Theologia and the ideologia of language, nation and gender – Gateway to the future from a deconstructed past - Aarde, Andries van (HTS teologiese studies, 2017)
The article is a contribution to the centennial celebration of the Faculty of Theology at the University of Pretoria. It forms part of the section in the programme titled ‘Ethos – Critical perspectives on our past and a gateway to our future’ and is dedicated to Yolanda Dreyer who was the first female professor appointed in the Faculty of Theology of the University of Pretoria. The article reflects on aspects of the present-day populist discourse in South Africa and globally, which is enhanced by neonationalistic separatism. The following issues are critically discussed: homophobia regarding sexual minorities, a lack of sensitivity for the negative effects of male domination and the objection to English as the lingua franca for teaching. These aspects are assessed against the background of the Derridean notion of ‘deconstruction’ and the contributions of the first professors employed in the Faculty of Theology since its inception in 2017.